The Use of Herbal Medicines for the Prevention of Glucocorticoid-Induced Osteoporosis - Zhang, Leiming; Li, Xiaoli; Ying, Tianhao; Wang, Tian; Fu, Fenghua (Frontiers in Endocrinology, 2021)
Glucocorticoids are drugs that are widely used to suppress inflammation and the activation of the immune system. However, the prolonged use or at high doses of glucocorticoid can result in adverse side effects including osteoporosis, bone loss, and an increased risk of fracture. A number of compounds derived from natural plant sources have been reported to exert anti-inflammatory activity by interacting with the glucocorticoid receptor (GR), likely owing to their chemical similarity to glucocorticoids, or by regulating GR, without a concomitant risk of treatment-related side effects such as osteoporosis. Other herbal compounds can counteract the pathogenic processes underlying glucocorticoid-induced osteoporosis (GIOP) by regulating homeostatic bone metabolic processes. Herein, we systematically searched the PubMed, Embase, and Cochrane library databases to identify articles discussing such compounds published as of May 01, 2021. Compounds reported to exert anti-inflammatory glucocorticoid-like activity without inducing GIOP include escin, ginsenosides, and glycyrrhizic acid, while compounds reported to alleviate GIOP by improving osteoblast function or modulating steroid hormone synthesis include tanshinol and icariin.